1970
DOI: 10.1111/j.2044-8295.1970.tb02797.x
|View full text |Cite
|
Sign up to set email alerts
|

The Semantic Function of Negatives and Passives

Abstract: The hypothesis was tested that syntactic constructions would be easier to deal with when they were being used for their natural semantic function rather than for an unnatural function. The experimental task required subjects to decide whether pairs of sentences had the same or a different meaning. The results confirmed the prediction that deciding about pairs of affirmative and negative sentences would be relatively facilitated when the negative was performing its natural function of signalling a change of mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
4

Year Published

1975
1975
1982
1982

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 3 publications
(3 reference statements)
0
9
0
4
Order By: Relevance
“…For example, the sentence "It is not a crime to smoke marijuana, but it is a crime to sell it" has a negative phrase which might clarify an issue. Such anargument has been made by several researchers (Green, 1970;Wason, 1965), and in these cases, negative sentences have been found to enhance comprehension.…”
Section: Negationmentioning
confidence: 96%
“…For example, the sentence "It is not a crime to smoke marijuana, but it is a crime to sell it" has a negative phrase which might clarify an issue. Such anargument has been made by several researchers (Green, 1970;Wason, 1965), and in these cases, negative sentences have been found to enhance comprehension.…”
Section: Negationmentioning
confidence: 96%
“…In recent years a number of studies have shown that logical negation serves to increase the processing time required in a variety of classification tasks (e .g., Chase & Clark, 1972;Greene, 1970;Meyer, 1973;Trabasso, 1970;Wason, 1959). For example, Howard (1972) required subjects to classify logical symbols corresponding to the four information conditions discussed by Wason and Trabasso.…”
mentioning
confidence: 99%
“…This can be interpreted in terms of the hypothesis that the function of the negative form is to negate a previously assumed positive proposition and that when a sentence does not have this function (as here) it is more difficult to process (Greene, 1970). However, the finding that the negated sentence type presented the most difficult discrimination is not quite so predictable.…”
Section: Discussionmentioning
confidence: 75%
“…However, the finding that the negated sentence type presented the most difficult discrimination is not quite so predictable. This can be interpreted in terms of the hypothesis that the function of the negative form is to negate a previously assumed positive proposition and that when a sentence does not have this function (as here) it is more difficult to process (Greene, 1970). Donaldson (1970) and de Villiers & Flusberg (1 975) have produced evidence that young children find descriptions with negative referents very difficult to complete; though more recent data from Watson (1979) suggest that the effect can be mitigated.…”
Section: Discussionmentioning
confidence: 82%